Workshop on index based flood insurance: Testing business model in agricultural risk management - International Water Management Institute (International Water Management Institute, 2017)
Growing population, poor management of land and water resources, and increased exposure to extreme climatic events have left a large number of people vulnerable to floods. Floods lead to widespread destruction and human tragedy, severely impacting infrastructure, agriculture and ecosystems. Agricultural communities are subjected to severe economic pressure from flood-induced losses. However, over the last few decades, evidence has emerged that a broader approach through planning, building regulation and early warning systems can significantly reduce flood losses. Index- based flood insurance (IBFI) is one such solution that is both cost-effective and can better target post- disaster relief to compensate agricultural losses. The event was coordinated by Dr. Giriraj Amarnath (Sub Theme Leader: Water-related Disaster and Risk Management of IWMI) and the workshop was inaugurated by Sh. Anil Sinha (Senior Advisor & Mentor, Hazard Risk Management and Climate Change Adaptation and former VC, BSDMA), and opening remarks from Mr. Jeremy Bird (Director General of IWMI), Dr. L S Rathore, (former DG, Indian Meteorological Department (IMD)), and Dr. Alok Sikka (IWMI India Representative), who gave the welcome remarks. Participants from government bodies, agricultural banks, public and private insurance companies involved in the workshop to exchange ideas and expertise on development of Business model for Index-Based Flood Insurance (IBFI). Experts attended the workshop from multiple organizations including National Disaster Management Authority (NDMA), Indian Council of Agricultural Research (ICAR), Indian Agriculture Research Institute (IARI), NABARD, UN-ESCAP (New Delhi), Agriculture Insurance Company of India (AIC), CCAFS, CDOT, Bajaj Allianz, ICICI Lombard, HDFC ERGO, Royal Sundaram General Insurance, Skymet Weather Service Pvt. Ltd. and others. The objective of the workshop is to present the progress of the IBFI business model and discussion about improving the value-chain process in index insurance and way forward in implementation of the product in 2017 monsoon season in Bihar. To briefly discuss existing business modeling approaches and the case studies and obtain feedback from participants, three presentations (presented by Dr. Giriraj Amaranth of IWMI, Dr. Ravinder Malik of IWMI and Dr. Avinandan Taron of IWMI) were presented respectively on Project progress, IBFI Business Model and Economic analysis and Business model implementation in Indian Scenario. During the workshop, group discussions were supported by broad communications between participants from government bodies, private insurers, public and private banks and others.